Relationship of fiber consumption with obesity and gut health in students of SMAN 3 Kupang City - Dupe, Freny R; Lada, Christina Olly; Datta, Frans Umbu; Roga, Anderias Umbu; Handoyo, Nicholas E. (World Nutrition Journal, 2025)
Background: Fiber is a necessity that must be met to help maintain digestive health and prevent obesity. The easiest sources of fiber are vegetables and fruits. Objective: This study aims to determine the correlation of fiber consumption with obesity and gut health in students of SMAN 3 Kupang City.